"From teacher to teacher" requirement of current education (2021)
When conceiving education as a permanent process of living construction of the person and not only of preparation in the disciplines, the teacher plays again a very important role, since he teaches for the life. This is the reason why the present article tries to make teachers conscious of not only teaching contents in the classroom, but also, through pedagogy, cross a road that will let them become masters, and with regard to that, the best pedagogy is the one used by Jesus from Nazareth, master by excellence who transcended from the knowledge for the mind to experiences for the heart.